PENERAPAN MARKETING MIX DALAM PEMASARAN TELUR AYAM RAS DI KECAMATAN SANGATTA SELATAN (STUDI KASUS PADA PETERNAKAN PHILIPINES FARM) - Nursida Nursida; Muhammad Yazid Bustomi; Muhammad Yusuf Efendy (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Sangatta Selatan Sub-District, East Kutai District was one of the potential areas for the development of laying hens. The local farm that cultivates laying hens in this sub-district is Philipines Farm. The sustainability of a business requires the ability to face the market. Therefore, every businessman needs to implement the marketing mix. This study aims to determine the application of the marketing mix on marketing eggs of laying hens at the Philipines Farm in the South Sangatta Sub-District. This research was carried out in 2021 at the Philipines Farm by using a case study method. The results showed that the application of the marketing mix in marketing eggs of laying hens at the Philippines farm was good level with a value of 30. The application of the marketing mix in the aspect of place and price was a very good level, with scores of each 8 and 10. Based on these results, businessmen were expected to maintain the performance of instruments of place and price. Meanwhile, the implementation of product and promotion aspects was good enough level with scores of 7 and 5. The strategy could be used by improving the performance of the instrument in product and promotion aspects.